Quantitative analysis in archaeology - VanPool, Todd L., 1968-; Leonard, Robert D. (Chichester, West Sussex, U.K. : Wiley-Blackwell, 2011)
'Quantitative analysis in archaeology introduces the application of quantitative methods in archaeology. It outlines conceptual and statistical principles, illustrates their application, and provides problem sets for practice. Discusses both methodological frameworks and quantitative methods of archaeological analysis. Presents statistical material in a clear and straightforward manner ideal for students and professionals in the field. Includes illustrative problem sets and practice exercises in each chapter that reinforce practical application of quantitative analysis'--Provided by publisher.
'This text is an ideal introduction to the use of quantitative methods in archaeology. It outlines conceptual and statistical principles, illustrates their application, and provides problem sets for practice. Statistical techniques are presented in a clear and straightforward manner throughout, and the careful balance between introduction of key concepts and their application to archaeological data is perfectly suited for both students and professionals in the field. Quantitative analysis in archaeology is the most comprehensive review available of the essentials of measurement in archaeology, and it includes coverage of methods and techniques valuable to archaeologists but not found in other texts'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Archaeology -- Methodology; Quantitative research; Archaeology -- Research